1999
DOI: 10.1046/j.1365-2273.1999.00234.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of conductive hearing loss on the vestibulo-collic reflex

Abstract: The vestibulo-collic reflex represents a promising test for evaluating the integrity of otolith function. We have investigated the threshold of this response in a group of normal subjects, and the effect of a conductive hearing loss. A positive response was recorded in 31 of 32 normal subjects. The threshold of the vestibulo-collic reflex varied from 80 to 97 dBHL in these subjects with a 95% response rate at a threshold at 96 dBHL. A total of 23 ears with a conductive hearing loss in 17 patients were also inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 4 publications
1
26
0
3
Order By: Relevance
“…The following were the exclusion criteria: (1) medical history of other neurological disorders, (2) familial history of auditory or vestibular dysfunction, (3) past history of excessive noise exposure, head injury or exposure to ototoxic drugs, (4) sensorineural hearing loss except for presbycusis, (5) the existence of air-bone gap (more than 10 dB) [8], (6) abnormal findings on neurological examinations except for vestibular dysfunction, (7) difficulty in maintaining muscle activity at a sufficient level [electromyographic (EMG) activity [150 lV].…”
Section: Patientsmentioning
confidence: 99%
“…The following were the exclusion criteria: (1) medical history of other neurological disorders, (2) familial history of auditory or vestibular dysfunction, (3) past history of excessive noise exposure, head injury or exposure to ototoxic drugs, (4) sensorineural hearing loss except for presbycusis, (5) the existence of air-bone gap (more than 10 dB) [8], (6) abnormal findings on neurological examinations except for vestibular dysfunction, (7) difficulty in maintaining muscle activity at a sufficient level [electromyographic (EMG) activity [150 lV].…”
Section: Patientsmentioning
confidence: 99%
“…cVEMPs are not dependent upon hearing and are therefore present in patients with sensorineural hearing loss. However, they are attenuated or absent in patients with conductive hearing loss, as the air-conducted stimulus requires efficient transfer through the outer and middle ear to the vestibule (Bath et al, 1999). To overcome this disadvantage of air-conducted sound, Halmagyi et al (1995) demonstrated that cVEMPs could also be elicited by tapping the forehead with a clinical reflex hammer.…”
Section: Introductionmentioning
confidence: 98%
“…To record VEMP, airconducted sound is usually applied. Then, the integrity of the middle ear conductive mechanism [5,8] is required. It is often difficult to elicit this vestibulardependent response in subjects with conductive hearing loss.…”
Section: Introductionmentioning
confidence: 99%